Pengaruh Bantuan Sosial Tunai (BST) terhadap Perilaku Konsumtif Masyarakat di Desa Dunggala Kecamatan Tibawa - Aldiyanto Abidju; Sri Endang Saleh; Roy Hasiru; Frahmawati Bumulo; Ardiansyah Ardiansyah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study wasconducted in dunggala village, tibawa subdistrict, gorontalo regency. The objective Is to determine the effect of clash social assistance (BST) on the consumer behavior of the comunity in dungala vilage. This study employed a quantitative aproach. Data were collected thourgh observation, interviews , questionnaires, and documention. The population consisted of 98 individuals, with a sample of respondents. The date were analyzed using simple linier regresion. The results indicate that cash social assistance (BST)affects the consumer behavior of the comunty in dunggala vilage. Based on the cofficient of the determination (R square), a value of 0, 326 was obtained, indicating that 67,4% of the variabilty in consumer behavior can be explained by the cash social assistance variable, while the remaning 6,74% is affected by other variabels not examined in this study.